(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: There are two manners of death: Naturalwhere death is entirely caused by disease or ageing process, where poison or trauma does not take part to cause it and Unnatural- where death is sudden, suspicious, unexpected, litigious, unexplained and unattended either due to poison or trauma. Accident, homicide and suicide are the three unnatural manners of death. Death due to intentional injuries such as homicide or suicide and unintentional injuries of accidental manner, such as in transportation injury or industrial or machinery mishaps constitute unnatural deaths. Suicidal deaths are the acts or an instance of taking one’s own life voluntarily and intentionally especially by a person of years of discretion and of sound mind. Objective: To ascertain the medico-legal issues and sociodemographic profile of suicidal death cases occuerd in Dhaka City. Materials and Methods: A record based cross sectional study of postmortems was performed at the mortuary of the Forensic Medicine Department of Dhaka Medical College (DMC) from August 2009 to July 2010. A total of 3,337 cases brought to DMC mortuary from the south-eastern part of Dhaka district during this period were included in this study and thereafter 827 suicidal deaths were considered for this study. Results: A total of 3,337 unnatural deaths (accidents, suicide and homicide) were reported at the mortuary of the Forensic Medicine Department of Dhaka Medical College (DMC) during the period of August 2009 to July 2010. This study revealed that 827(24.78%) individual committed suicide out of 3337 cases. There was a predominance of Muslims 779(94.19%), males 481(58.16%) over females 346(41.84%) in committing suicide. Majority of the victims belonged to the age group of 21-30 years in both sexes. Out of these suicidal cases, 318(38.45%) victims committed suicide by hanging. The other methods used for suicide were Organophosphorus compound poisoning (OPC) by 238(28.79%) victims, poisoning from other substances like Opiates, Ethanol, Methanol, Rodenticide, Barbiturate etc by 267 (32.28%); 3(0.36%) cases were identified as burn and 1 (0.12%) by firearm. Conclusion: Suicide is the second most common manner of unnatural death flanked by accident and homicide. Suicide is one of the most multifaceted and media-sensitive phenomena. Suicide by hanging is an increasingly common method. All stakeholders such as government along with private agencies, non-government organizations, public health departments, social workers, community, religious leaders and media can take a leading step to prevent suicide Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 33-36